An analysis study of sexual offenses regarding rape, statutory rape and sexual harassment in Malaysia, United Kingdom, Australia and India / Norshafinas Shamsudin … [et al.] - Shamsudin, Norshafinas; Ahmad, Nor Ahyani; Paisan, Anis Suraya; Harun, Siti Noraini (2011)
Cases on sexual offenses particularly on rape, statutory rape and sexual harassment in Malaysia keep increasing nowadays. Almost every day, cases on those offenses have been the major news being reported in the newspapers and magazines throughout this country. This research therefore has been conducted in order to study on laws governing sexual offences particularly on rape, statutory rape and sexual harassment in Malaysia. This research will define what sexual offence is and what offences can be regarded as sexual offences. This research also will explain what law is used to govern sexual offences in different countries namely Malaysia, United Kingdom, Australia and India. Subsequently, this research will scrutinize the relevancy, effectiveness and comprehensiveness of law governing sexual offences in Malaysia. Three major issues will be put forward which are protection of man against offence of rape in Malaysia. Secondly, it is necessity to impose equal punishment against man and woman who commits statutory rape. Thirdly, need of special provision in Penal Code for offence of sexual harassment. Comparison will be made between law adopted in Malaysia and law adopted in United Kingdom, Australia and India. This study further will provide few recommendations to improve Malaysian law on sexual offences particularly on offence of rape, statutory rape and sexual harassment.